Classification and effectiveness of different oxygenation goals in mechanically ventilated critically ill patients: network meta-analysis of randomised controlled trials. Issue 3 (30th September 2021) - Zhao, Xu; Xiao, Huaping; Dai, Feng; Brodie, Daniel; Meng, Lingzhong
Background: The optimal oxygenation in mechanically ventilated critically ill patients remains unclear. Methods: We performed a systematic review of randomised controlled trials (RCTs) with the aim to classify oxygenation goals and investigate their relative effectiveness. RCTs investigating different oxygenation goal-directed mechanical ventilation in critically ill adult patients were eligible for the analysis. The trinary classification classified oxygenation goals into conservative (partial pressure of arterial oxygen ( P aO2 ) 55–90 mmHg), moderate ( P aO2 90–150 mmHg) and liberal ( P aO2 >150 mmHg). The quadruple classification further divided the conservative goal from the trinary classification into far-conservative ( P aO2 55–70 mmHg) and conservative ( P aO2 70–90 mmHg) goals. The primary outcome was 30-day mortality. The secondary outcomes included intensive care unit, hospital and 90-day mortalities. The effectiveness was estimated by the relative risk and 95% credible interval (CrI) using network meta-analysis and visualised using surface under the cumulative ranking curve (SUCRA) scores and survival curves. Results: We identified eight eligible studies involving 2532 patients. There were no differences between conservative and moderate goals (relative risk 1.08, 95% CrI 0.85–1.36; moderate quality), between moderate and liberal goals (relative risk 0.83, 95% CrI 0.61–1.10; low quality) or between conservative and liberal goals (relative risk 0.89, 95% CrI 0.61–1.30; low quality) based on the trinary classification. There were no differences in secondary outcomes among the different goals. The results were consistent between the trinary and quadruple classifications. The SUCRA scores and survival curves suggested that the moderate goal in the trinary and quadruple classifications and the conservative goal in the quadruple classification may be superior to the liberal and far-conservative goals. Conclusions: Different oxygenation goals do not lead to different mortalities in mechanically ventilated critically ill patients. The potential superiority of maintaining P aO2 in the range 70–150 mmHg remains to be validated. The available evidence does not suggest different effects on mortality among different oxygenation goals in mechanically ventilated critically ill patients. The P aO2 range of 70–150 mmHg is potentially superior but remains to be validated. https://bit.ly/3qtMc1D